Cytological spectrum in patients of gastro-esophageal reflux disease: A prospective study in a tertiary care institute (International Journal of Biomedical Research, 2017)
Gastroesophageal reflux disease (GERD) is defined as reflux of gastric contents into mouth resulting in restrosternal burning sensation. Aims: This prospective study was undertaken with the aim to assess the cytological spectrum in esophageal brushings taken from patients with GERD and there correlation with esophageal biopsy. Method: Esophageal brushings and biopsies were taken from 150 patients of GERD and 50 controls. GERD cases were defined by the presence of classical symptoms of heart burn and/or acid regurgitation. Endoscopically, GERD cases were subdivided into erosive reflux disease (ERD) and non-erosive reflux disease (NERD). Three cytological parameters studied in esophageal brushings were reactive changes, presence or absence of inflammation and presence or absence of parabasal cells. Results: The most common finding was reactive changes with inflammation (56 cases, 37.33%) followed by inflammatory smears in 12 (8%) patients. Parabasal cells were not seen in any of the subjects with GERD. Presence of reactive changes with inflammation revealed a statistically significant correlation between GERD patients and controls (p 0.05). However, the presence of inflammatory cells did not reveal a statistical significance. (p=0.136). The sensitivity of cytology in our study was 68% and specificity was 95.12%. Conclusion: Cytology cannot be truly relied upon and can only be used as an adjunct to histpathology with both being complementary to each other.